Application of yuba film as frozen dumpling wrappers. (November 2021) - Yang, Fan; Kim, Yookyung
Abstract: To determine whether modified frozen yuba film (soy protein-lipid film) can be used as wrappers rather than using frozen wheat dumpling wrappers (WDW), transglutaminase (TGase), and sodium pyrophosphate were used to improve the mechanical properties and reduce protein damage during freezing, respectively. Three yuba films were prepared: untreated yuba film (UY), treated with TGase and heat (TGHY), and treated with TGase, heat, and sodium pyrophosphate (TGHPY). FT-IR confirmed the cross-linking effect of TGase at 1623 and 1535 cm −1 and the plasticizing effect of sodium pyrophosphate on TGHY at 1040 cm −1 . SDS-PAGE showed that the α, α, β, and BS bands in UY decreased during freezing, whereas cross-linking promoted in TGHY and TGHPY reduced the soluble protein band. After 28 d of frozen storage, the tensile strength of all samples increased, and the elongation at break (EB) decreased, except for TGHPY, which had the most stable and highest EB during storage. Microscopic analysis revealed that the surface of TGHPY appeared smooth and uniform during frozen storage. When dumplings were made from frozen films, TGHPY wrappings had a lower cooking loss and better elasticity and cohesiveness than the TGHY wrappings. Transglutaminase and sodium pyrophosphate improved yuba films for preparing frozen dumpling wrappers as gluten-free products. Highlights: We attempted to improve the properties of yuba films by using additives in the wrappers. Transglutaminase improves the mechanical properties of yuba through cross-linking. Sodium pyrophosphate reduces protein damage during freezing. Yuba films can be used as gluten-free frozen dumpling wrappers.